Clinicopathological features of bi-ventricular cardiac intimal sarcoma—Report of an autopsy case. Issue 4 (October 2017) - Tamaki, Takehiro; Suzuki, Makoto; Umezu, Ryuta; Utanohara, Yuko; Mahara, Keitaro; Takanashi, Shuichiro; Murai, Tatsuya; Tomoike, Hitonobu
Abstract: We present the clinicopathological characteristics of primary cardiac intimal sarcoma which was widely spread throughout bi-ventricles. The patient had a wide range of clinical manifestations starting with left-sided heart failure then finally developing refractory right-sided heart failure during 44 months of follow-up. <Learning objective: The present clinicopathological characteristics with a wide spectrum of clinical features may provide a pivotal insight into understanding primary cardiac intimal sarcoma.>